CBASP@YoungAge Behandlungsprogramm für Depressionen im Kindes- und Jugendalter - Dippel, Nele (Beltz Juventa, 2023)
Depression in children and adolescents often has its roots in difficult family relationships. The therapy approach CBASP (Cognitive Behavioural Analysis System of Psychotherapy), which was developed especially for the treatment of chronic depression, has now been adapted for the therapy of children and adolescents in an age-sensitive way. The procedure is presented for the first time in this manual for therapeutic practice. The programme is aimed at depressive patients aged ten to 21 years in an outpatient setting. Difficult relationship experiences and current interpersonal problems are particularly addressed. The programme is modular and can be individually adapted to the course of the disorder and includes individual and joint sessions for patients and caregivers. The modules and interventions differ in age-appropriate approach and problem content and include attractively prepared working materials.